Globalization and Education: Designing Culturally Inclusive Curricula for a Connected World - Aoumeur Soufghalem (International Journal of Post Axial: Futuristic Teaching and Learning, 2024)
This research explores the impact of globalization on curriculum design and the implementation of culturally inclusive curricula. Through a mixed-methods approach, including quantitative surveys and qualitative interviews, the study examines how globalization shapes educational objectives and integrates global competencies and cultural perspectives into curricula. The findings highlight the positive effects of culturally inclusive curricula on students' intercultural competence and global awareness, demonstrating that such curricula effectively prepare students for the complexities of a globalized world. The research also identifies significant challenges in implementing these curricula, such as resource constraints, resistance to change, and varying levels of institutional support. These barriers often hinder the effective integration of diverse perspectives into educational frameworks. Despite these challenges, the study underscores the importance of embedding global competencies into curricula and provides recommendations for overcoming obstacles, including enhanced support systems and targeted professional development for educators. This research contributes to a deeper understanding of the role of globalization in shaping educational practices and offers practical insights for policymakers, educators, and curriculum designers. By addressing the identified challenges and leveraging best practices, educational systems can better support the development of a globally competent and culturally aware student body. Future research should continue to explore the long-term impacts of culturally inclusive education and refine strategies for effective implementation across diverse educational contexts